2018
DOI: 10.1007/s11274-018-2411-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and enzymatic potentialities of Bacillus sp. strains isolated from a polluted freshwater ecosystem in Cuba

Abstract: Genotypic and phenotypic characterization of Bacillus spp. from polluted freshwater has been poorly addressed. The objective of this research was to determine the diversity and enzymatic potentialities of Bacillus spp. strains isolated from the Almendares River. Bacilli strains from a polluted river were characterized by considering the production of extracellular enzymes using API ZYM. 14 strains were selected and identified using 16S rRNA, gyrB and aroE genes. Genotypic diversity of the Bacillus spp. strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Extensive studies have found that Bacillus sp. that produces amylase can improve water quality (Gigras, Sahai, & Gupta, 2002; Larrea‐Murrell et al., 2018). It is therefore of value to investigate and isolate amylase‐producing microorganisms from aquaculture water, and better apply them in aquaculture systems.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have found that Bacillus sp. that produces amylase can improve water quality (Gigras, Sahai, & Gupta, 2002; Larrea‐Murrell et al., 2018). It is therefore of value to investigate and isolate amylase‐producing microorganisms from aquaculture water, and better apply them in aquaculture systems.…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater lakes are extremely biodiverse natural water reservoirs, with many important recreational and landscape qualities [17] though freshwater environments have been studied to a lesser extent than marine ones [18]. In aquatic ecosystems, bacteria play an important role in degradation of the organic matter, assimilation of carbon, nitrogen, and phosphorus which are catalyzed by enzymes produced by microorganisms [19][20][21][22]. Furthermore, bioprospecting microbial diversity of freshwater lakes is important as they are an important source of microbes which produce diverse enzymes of agricultural and industrial importance, various bioactive compounds, etc.…”
Section: Discussionmentioning
confidence: 99%